The Million Hearts Initiative: CATALYZING UTILIZATION OF CARDIAC REHABILITATION AND ACCELERATING IMPLEMENTATION OF NEW CARE MODELS. Issue 5 (September 2020) - Wall, Hilary K.; Stolp, Haley; Wright, Janet S.; Ritchey, Matthew D.; Thomas, Randal J.; Ades, Philip A.; Sperling, Laurence S.
Abstract : Million Hearts and partners have been committed to raising national cardiac rehabilitation participation rates to a goal of 70%. Quality improvement tools, resources, and surveillance models have been developed in support. Efforts to enhance research programs and collaborative initiatives have created momentum to accelerate implementation of new care models. Abstract : Supplemental Digital Content is Available in the Text.Million Hearts and partners have been committed to raising national cardiac rehabilitation participation rates to a goal of 70%. Quality improvement tools, resources, and surveillance models have been developed in support. Efforts to enhance research programs and collaborative initiatives have created momentum to accelerate implementation of new care models.